From Countryside to City: How Land Property Rights Drive Migration in China - Lai, Juncheng (Transactions on Economics, Business and Management Research, 2024)
China’s remarkable economic surge since the 1970s hasn’t erased the pronounced economic disparities across different regions, most notably between rural and urban locales. Rooted in the historical division of land rights and usage stipulated by economic reforms, this urban-rural dichotomy has fostered varied development patterns in infrastructure, primary industries, and foreign trade and investment. At the core of this dichotomy is the contrasting landscape of land property rights—state ownership in urban areas with permissible leaseholds versus collective ownership in rural areas with restrictions on transfer or leasing. This paper investigates how these divergent land property rights regimes have engendered significant migration patterns, predominantly marked by rural to urban migration, in pursuit of better economic prospects. Through a meticulous examination of the Household Responsibility System (HRS) and subsequent agrarian reforms, this paper elucidates how partial property rights and restrictions on land transferability under HRS have had substantial repercussions on domestic migration. The analysis delineates how well-defined and secure property rights, as postulated by prominent theories of property rights, are instrumental in incentivizing migration. When operational, market mechanisms of land property rights enable farmers to lease their lands, thereby fostering migration by reducing the opportunity cost of leaving rural lands. Conversely, in the absence of robust property rights, government mechanisms often lead to forced land acquisitions sans adequate compensation, exacerbating rural-urban income disparities and propelling rural-urban migration. The paper expounds on the multifaceted implications of these migration patterns on economic opportunities, poverty alleviation, and urbanization in China. Additionally, it discusses the ripple effects of rural-urban migration on income disparity and the consequent socioeconomic repercussions. The findings shed light on the complex interrelationship between land property rights and migration, providing a nuanced understanding of China’s urbanization trajectory and its attendant rural-urban disparities. This analysis offers valuable insights for policy formulations aimed at addressing the systemic issues arising from the entrenched land property rights framework, and suggests a pathway towards a more balanced regional economic development and sustainable urbanization in China.